Memahami Karakteristik Psikologis Peserta Didik untuk Meningkatkan Proses Pembelajaran - Nur Anisah; Risnawati Rumatoras; Prihaten Maskhuliah (Journal Innovation In Education, 2025)
Understanding the psychological characteristics of students is a fundamental step to improve the effectiveness of the learning process. These characteristics include cognitive, emotional, social, and motivational aspects that affect how students absorb and process information. This article reviews educational psychology theories, such as Piaget's cognitive development theory, Maslow's basic needs, and Gardner's multiple intelligences, which are relevant in designing adaptive learning strategies. In addition, the importance of the teacher's role in understanding students' temperament, learning styles, and emotional and social needs is outlined to create an inclusive learning environment. This study uses a literature study approach to analyze related literature. The results show that the application of personalized learning approaches, such as problem-based learning (PBL) and differentiated learning, can improve students' motivation and learning outcomes. By understanding the unique characteristics of each student, educators can help them develop according to their individual potential and needs, thus creating an optimal and sustainable learning process.